Assessing the BIM-Lean Synergy Adoption Trends in the Malaysian Construction Sector: Benefits and Challenges - Mohd Noh, Nur Izzah; Ang , Peniel Soon Ern; Mohamed Salehin, Nur Ili Izyan; Osman, Mohamad Hairi; Yahya, Nur Faezah; Kasim, Narimah; Kumaran, NV; Tsai Kai Len, Joseph; Yi Lin, Pung; Imran Latif, Qadir Bux alias (Journal of Advanced Research Design, 2025)
Building Information Modelling (BIM) refers to a detailed digital depiction of a building, including its geometry and information for design and procurement purposes. Meanwhile, Lean Construction (LC) is an approach aiming to improve construction efficiency through waste reduction of time, resources and labour while maximising project potential value. Certainly, the construction industry promotes real, practical solutions over theoretical concepts. Despite previous global adoption of BIM-Lean synergy demonstrating benefits like increased profitability, cost and schedule control and risk reduction, most Malaysian construction sector is mostly unaware of these benefits. Thus, this study aims: i) to assess the level of awareness of lean implementation in Malaysian BIM construction projects and ii) to investigate the feasibility of BIM-Lean synergy in Malaysian construction projects. This research employed qualitative methods, which include semi-structured interviews with 12 industry professionals from Grade 3 to Grade 7 contractors and an engineering solution consultant in Selangor. Findings interpreted that all respondents agreed that the integration of BIM-Lean synergy will substantially impact the construction sector over the next decade. The benefits include better communication and collaboration, more on-site monitoring and fewer inefficient process layouts and errors. However, challenges include a lack of study of synergy functionality, low contractor acceptance and high software expenses. Regardless of this, BIM-Lean synergy is feasible in Malaysia with strong top-down government support and collaboration with industry players.